Sequential embryo transfer versus double cleavage-stage embryo or double blastocyst transfer in patients with recurrent implantation failure with frozen-thawed embryo transfer cycles: a cohort study - Gao, Jiangman; Yuan, Yifeng; Li, Jia; Tian, Tian; Lian, Ying; Liu, Ping; Li, Rong; Qiao, Jie; Long, Xiaoyu; Wang, Haiyan (Frontiers in Endocrinology, 2023)
Background Recurrent implantation failure (RIF) is more common among patients receiving assisted reproductive treatment. Many efforts have been made to increase the incidence of clinical pregnancy among patients with RIF. The effect of the sequential transfer procedure, a two-step interval transfer of a cleavage-stage embryo followed by a blastocyst in one transfer cycle, on the clinical outcomes of RIF patients remains controversial. Methods In total, 1774 frozen-thawed embryo transfer (FET) cycles in RIF patients were included. Of these cycles, 302 were sequential embryo transfer (ET) cycles, 979 were double day 3 cleavage-stage ET cycles, and 493 were double blastocyst ET cycles. The primary outcomes were the rates of implantation, clinical pregnancy and multiple pregnancy, and the secondary outcomes were the rates of hCG positive, early miscarriage and ectopic pregnancy. Results The implantation, hCG positive, and clinical pregnancy rates in the sequential ET group (32.1%, 58.9%, 50.7%) were significantly higher than those in the day 3 cleavage-stage ET group (24.9%, 46.5%, 40.4%) and were similar to those in the blastocyst transfer group (30.1%, 56.4%, 47.1%). The early miscarriage rate in the blastocyst transfer group was significantly higher than that in the cleavage-stage ET group (17.2% vs. 8.1%, P <0.05), while the ectopic pregnancy rate in the blastocyst transfer group was significantly lower than that in the cleavage-stage ET group (0.4% vs. 3.0%, P <0.05). The multiple pregnancy rate in the sequential ET group was significantly lower than that in the cleavage-stage ET group (17.0% vs. 25.5%, P <0.05) and the blastocyst transfer group (17.0% vs. 27.6%, P <0.05). When cycles of blastocyst culture failure were excluded, the clinical pregnancy rate was significantly higher (55.7% vs. 47.1%, P <0.05), and the early miscarriage rate and multiple pregnancy rate were significantly lower (8.5% vs. 17.2%, 17.7% vs. 27.6%; P <0.05, respectively) in the sequential ET group than in the double blastocyst ET group. Conclusions Sequential embryo transfer in FET cycles could improve the clinical outcomes of patients with RIF.